Molecular dynamics of Triton X surfactant molecules with different PEO chain lengths at the air/water interface - Jin Peng (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2023)
This paper focuses on the structural properties and interface behavior of TX-5, TX-114, and TX-100 molecules at the air/water interface. The results of the density profile show that the polar O atoms of the three TX molecules are basically located on the water surface, and the whole TX molecule is almost parallel to the water surface. The results of the order parameters show that the order parameters of the three TX molecules on the interface are similar and relatively ordered. The TX-100 molecule has the largest gauche defect value. The hydration number of TX molecules at the interface was similar to that of TX molecules in micelles, and the hydration number of PEO chains showed obvious zigzag changes. The research of this paper provides a reference for the further development of TX series micellar and surfactant molecules in the field of pharmaceutical and daily use.